2017
DOI: 10.1186/s13024-017-0153-4
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic LRRK2 variants are gain-of-function mutations that enhance LRRK2-mediated repression of β-catenin signaling

Abstract: Background LRRK2 mutations and risk variants increase susceptibility to inherited and idiopathic Parkinson’s disease, while recent studies have identified potential protective variants. This, and the fact that LRRK2 mutation carriers develop symptoms and brain pathology almost indistinguishable from idiopathic Parkinson’s disease, has led to enormous interest in this protein. LRRK2 has been implicated in a range of cellular events, but key among them is canonical Wnt signalling, which results in increased leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(79 citation statements)
references
References 95 publications
3
76
0
Order By: Relevance
“…Activation of Wnt signalling plays a role in producing regionally homogeneous populations of NSCs and neurons. For instance, pivotal genes whose mutations are linked to PD negatively impact on WβC‐signalling (Berwick and Harvey, , Berwick et al, ), resulting in an inhibition of the ability of human induced pluripotent cells (iPSCs) to differentiate into DAergic neurons (Awad et al, ; Momcilovic et al, ; Moya et al, ). Specifically, downregulation of WβC‐signalling in iPSC‐derived NSCs due to a GBA1 mutation resulted in a dramatic decrease in the survival of DAergic progenitors (Awad et al, ) .…”
Section: Activators and Inhibitors Of The “Wnt‐signalosome” And Theirmentioning
confidence: 99%
“…Activation of Wnt signalling plays a role in producing regionally homogeneous populations of NSCs and neurons. For instance, pivotal genes whose mutations are linked to PD negatively impact on WβC‐signalling (Berwick and Harvey, , Berwick et al, ), resulting in an inhibition of the ability of human induced pluripotent cells (iPSCs) to differentiate into DAergic neurons (Awad et al, ; Momcilovic et al, ; Moya et al, ). Specifically, downregulation of WβC‐signalling in iPSC‐derived NSCs due to a GBA1 mutation resulted in a dramatic decrease in the survival of DAergic progenitors (Awad et al, ) .…”
Section: Activators and Inhibitors Of The “Wnt‐signalosome” And Theirmentioning
confidence: 99%
“…Finally, the crucial link between inflammation and PD is further exemplified by the fact that key PD-associated genes, such as α-Syn (SNCA), PARK2, deglycase (DJ-1), leucine-rich repeat kinase 2 (LRRK2), and glucocerebrosidase (GBA) are all expressed in immune cells, suggesting their potential to modulate inflammation (Dzamko et al, 2015 ). Reciprocally, an increasing number of PD-related genes including LRRK2, VPS35, PINK1, UCHL-1, Parkin, ATP6AP2, and GBA modulate the canonical Wnt pathway (Berwick et al, 2017 and Refs. therein), further underlinying a critical Wnt/inflammatory connection in PD (Marchetti and Pluchino, 2013 ).…”
Section: Genetic Mutations Inflammation and Mda Neurodegeneration: Mmentioning
confidence: 99%
“…Despite evidence of the relationship between LRRK2 and Wnt signaling, the specific effects of LRRK2 on downstream components remain unclear. Recently, Berwick et al [52] reported that the primary role of LRRK2 in the canonical Wnt signaling pathway is β-catenin repression: loss of LRRK2 increases Wnt/β-catenin activity, whereas overexpressed LRRK2 binds and represses β-catenin. Another study assessing the effect of LRRK2 on Wnt/planar cell polarity (PCP) signaling indicated that LRRK2 activates this pathway via interactions with multiple Wnt/PCP signaling components [53].…”
Section: Lrrk2 Mutations and Their Mechanisms Of Actionmentioning
confidence: 99%